PERSEPSI MASYARAKAT TERHADAP BANK SYARIAH (STUDI KASUS DI DESA TANJUNG AGUNG KECAMATAN TANJUNG AGUNG PALIK KABUPATEN BENGKULU UTARA) - Dharma Setiawan; Novi Permata Novi Permata; Amir Mukadar; Subandrio Subandrio (Universitas Muhammadiyah Bengkulu, 2024)
This research is qualitative research. The data analysis technique used uses interactive analysis techniques, in which there are three components, namely data reduction, data presentation and conclusion drawing. The results of this research identify that it is very important to disseminate information to the community about the Vision and Mission of Sharia Banking, especially for the people of Tanjung Agung village, Tanjung Agung Palik District, North Bengkulu Regency, with a population of 1,511 people. It turns out that there are still many who do not understand or comprehend Islamic banking and the systems used. within the Islamic bank itself. Due to the lack of socialization from sharia banks towards the community, especially the people of Tanjung Agung village, Tanjung Agung Palik District, North Bengkulu Regency, this has made people less interested in sharia banks and prefer conventional banks for the reason that they first knew about the existence of conventional banks. Keywords: Public Perception, Sharia Bank